Terpenoids from Conyza Linifolia - S. Hussein, Nadia; A. Ahmed, Ahmed; Spaller, Mark; J. Mabry, Tom (Asian Journal of Chemistry, 2010)
From the terpenoid extract of Conyza linifolia a rare daucane, an eudesmanolide and a triterpene were isolated.